The Effect of Teaching Programme on Knowledge and Caring Practice of Intra-Aortic Balloon Pump Patient Among ICU Staff Nurses - Yasmeen Ghafoor, Hajra Sarwar, M. Afzal, Adnan Yaqoob, Sadia Khan, Samreena Ghafoor, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The intra-aortic balloon is the most commonly used of all circulatory assist device provide the circulatory support for cardiac patients experiencing hemodynamic instability due to cardiogenic shock and myocardial infraction. during angioplasty for those patients on very high risk, and also used during coronary artery bypass grafting (CABG). During this device nurses play a very important role to provide care. nurse knowledge and practices are very helpful to soon recovery and prevent from complication. Educational programme is necessary for upgrading the nurse knowledge and skills. Objectives: Assess the knowledge & practices of nurses regarding IABP in Cardiac patient and introduce the IABP practice standardized guidelines on care of patent with IABP among ICU nurses. Material and Method: A Qausi experimental study design was used from October to December 2018. The data was collected from 40 nurses of ICU, CCU of Punjab Institute of Cardiology, Lahore The sampling technique was used convenient sampling. Data was entered and analyzed by using SPSS version 23, finding presented as frequencies, proportions and comparisons of means using a paired sample t-test will analyze. Differences were considered statistically significant if p < 0.05. Results: In this shown that the majority of had nurses had poor knowledge and practice related to intra-aortic balloon pump before educational programme which has been enhanced after educational session of this study. Conclusion: Empowerment of cardiac critical care nurse’s knowledge and practice would have knowledge and skillful impression upon their knowledge and practices.